National Health Interview Survey, 1989: Diabetes Supplement ([Verlag nicht ermittelbar], 1993)
The basic purpose of the National Health Interview Survey (NHIS) is to obtain information about the amount and distribution of illness, its effects in terms of disability and chronic impairments, and the kinds of health services people receive. Each year, the National Center for Health Statistics conducts the NHIS, a personal interview household survey that uses a nationwide sample of the civilian, noninstitutionalized population of the United States. The NHIS includes a core set of questions that remains virtually unchanged across years on a variety of sociodemographic and health-related concerns. In addition, one or more current health topics is selected for special emphasis annually. In 1989, the NHIS included an extensive set of questions, asked of each identified and self-confirmed adult diabetic in an interviewed family, on dietary practices, health care usage, use of medication, and other related subjects. In addition, in half of the responding families, an adult sample person was randomly selected to respond to a series of questions on diabetes risk factors. If the selected sample person was a diabetic, the questions were asked within the context of the detailed questions on diabetes health practices and knowledge mentioned above. This collection also contains data from the basic questionnaire (see NATIONAL HEALTH INTERVIEW SURVEY, 1989 [ICPSR 9583]), including age, sex, race, marital status, education, veteran status, income, family relationship, self-reported health status, and activity limitations, and the number of bed days, doctor visits, and hospital stays in the previous year.